Fluorinated benzenesulfonamide anticancer inhibitors of carbonic anhydrase IX exhibit lower toxic effects on zebrafish embryonic development than ethoxzolamide. (3rd July 2017) - Kazokaitė, Justina; Aspatwar, Ashok; Kairys, Visvaldas; Parkkila, Seppo; Matulis, Daumantas
Abstract: The toxic effects of two recently discovered inhibitors (VD12-09 andVD11-4-2 ) that selectively and with extraordinary strong, picomolar binding affinity to human carbonic anhydrase (CA) isoform IX were investigated on zebrafish embryonic development. CA IX has been recently introduced as an anticancer target since it is highly overexpressed in numerous human cancers but nearly absent in normal tissues. Morphological changes in zebrafish treated by the compounds were studied by light-field microscopy and histological analysis. Homology models of zebrafish CA II and CA IX were built to identify the conserved amino acid residues in the active site of zebrafish CAs. The toxicity studies here showed that the LC 50 values at 120 hours post-fertilization (hpf) were 13 μM forVD12-09, 120 μM forVD11-4-2, and 9 μM for ethoxzolamide (EZA ), a non-selective CA inhibitor commonly used as a drug in clinics. Thus, EZA was the most toxic of the three compounds. The zebrafish embryos exposed to LC50 doses ofVD12-09 andVD11-4-2 showed fewer phenotypic abnormalities compared with the embryos exposed to the corresponding dose ofEZA . Histochemical studies did not show any gross morphological changes in the embryos treated withVD12-09 andVD11-4-2 unlikeEZA . The results of our study indicate that the compounds exhibited 10-fold lower toxicity and induced fewer side effects in zebrafish thanEZA . Therefore, the exposure toVD11-4-2 andVD12-09 at concentrations below LC50 did not lead to deleterious effects on the zebrafish embryonic development and thus both inhibitors may be further developed as drugs.